182k views
1 vote
Solve each system of equations algebraically x-y=6 y=-1

User EoinS
by
5.8k points

2 Answers

1 vote

Answer:

x-(-1)=6

-x=6

-x/-1 6/-1

x=-6

User Totallyuneekname
by
6.5k points
3 votes

Answer:

Therefore, the solution of the system of equations will be:


x=5,\:y=-1

Explanation:

Given the system of equations


x-y=6;\:y=-1

solving


\begin{bmatrix}x-y=6\\ y=-1\end{bmatrix}


\mathrm{Subsititute\:}y=-1


\begin{bmatrix}x-\left(-1\right)=6\end{bmatrix}


\begin{bmatrix}x+1=6\end{bmatrix}

Isolate x for
x+1=6


x+1=6


x=5

Therefore, the solution of the system of equations will be:


x=5,\:y=-1

User Kathikeyan A
by
5.4k points